Qualidade microbiológica de ostras (crassostrea sp) e de águas coletadas em cultivos e em bancos naturais de cananéia (SP) - Ballesteros, Eliete Rodrigues [UNESP]; Andrade, Vanessada Costa [UNESP]; Barbieri, Edison; Pinto, Aline Bartelochi [UNESP]; Deoliveira, Raphaela Sanches [UNESP]; De Oliveira, Ana Júlia Fernandes Cardoso [UNESP] (My University, 2016)
The consumption of marine organisms, especially bivalve molluscs, might affect the human health, once that they concentrate in their tissues, suspended particles, including pathogenic microorganisms. Cananéia region is the largest oyster producer in the state of São Paulo, and in 1999 was founded the Cooperostra (Cooperative), which promotes the oysters depuration process in sterile tanks, leading to reduce and/or eliminate retained substances in their tissues. This study aims (i) evaluate the water quality in the adjacencies of the natural oysters’ beds and during the steps of the depuration process, through the determination of Escherichia coli, total coliforms and thermotolerant coliforms, and (ii)evaluate the contamination of Crassostrea sp by Salmonella sp., total coliforms, thermotolerant coliforms and Staphylococcus coagulase positive, in samples collected at Cooperostra and in natural oysters’ beds, assessing the contamination level of the organisms and the efficiency of the depuration process. The results show a reduce of Salmonella sp and coliforms densities in the oysters’ tissues after the depuration process. However, Staphylococcus coagulase positive shown high levels, which may be indicative of handling contamination. The Salmonella sp results were in agreement with RDC n12.
Microbial quality of oysters and waters from culture and natural banks in cananéia (SP)
Keywords: Bacteria; Depuration process; Microbiological quality; Oysters; Salmonella sp; Stahylococcus